Nonmonetary Awards and Innovation: Evidence from Winning China's Top Brand Contest - Lianfa Luo; Zhiming Cheng; Qingqing Ye; Yanjun Cheng; Russell Smyth; Zhiqing Yang; Le Zhang (Global Labor Organization (GLO), 2023)
We use the short-lived, but high-profile, China Top Brand Award to examine the causal effects of nonmonetary awards on firm innovation. To do so, we create a panel dataset by matching official China Top Brand Award recipients to the innovation outputs of listed companies. Results from difference-in-differences estimates show that firms that received the China Top Brand Award have a higher number, and better quality, of filed patents. We find that the positive effects of winning the China Top Brand Award on innovation outputs operate through higher government subsidies to winning firms. We also find that the positive effects of award-winning are stronger among state-owned enterprises, larger enterprises, and better-performing enterprises, as well as in provinces with stronger intellectual property rights protection. Our results are robust to a series of sensitivity checks.
Keywords: M2; O3; 330; China Top Brand Award; intellectual property rights; innovation outputs